RECONSTRUCTION OF EXTREME POVERTY ALLEVIATION POLICY IN LUMAJANG REGENCY BASED ON MAQĀSID AL-SHARĪ'AH: INTEGRATION OF PRODUCTIVE ZAKAT PROGRAMS, REGIONAL SOCIAL ASSISTANCE, AND COMMUNITY EMPOWERMENT - Aziz Abdillah; Muhammad Farid (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Extreme poverty remains a strategic challenge in regional development, including in Lumajang Regency. Various poverty alleviation policies have been implemented through local social assistance, zakat management, and community empowerment programs; however, their implementation tends to be fragmented and lacks sustainable integration. This study aims to analyze extreme poverty alleviation policies in Lumajang Regency and to reconstruct them using the Maqāṣid al-Sharī‘ah approach. This research employs a qualitative policy research method through document analysis of regional development planning documents, social assistance policies, and zakat programs, complemented by a review of recent scholarly literature. The findings indicate that current poverty alleviation policies are predominantly oriented toward consumptive assistance, which mainly fulfills the objective of preserving life (ḥifẓ al-nafs), while the objectives of economic empowerment (ḥifẓ al-māl) and human capacity development (ḥifẓ al-‘aql) have not been systematically integrated. This study concludes that a reconstruction of extreme poverty alleviation policies based on Maqāṣid al-Sharī‘ah is necessary through the integration of local social assistance, productive zakat, and community empowerment to achieve sustainable social welfare.